ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA UNTUK BERWIRAUSAHA DITINJAU DARI THEORY OF PLANNED BEHAVIOR: (Studi Kasus: Mahasiswa Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Katolik Santo Thomas) - Purba, Betniar (Jurnal Manajemen dan Bisnis, 2024)
This study aims to analyze what are the dominant factors that influence student interest in entrepreneurship. The benefits of research, for universiti, are expected to be able to stimulate student interest in entrepreneurship through the entrepreneurship curriculum offered. For acdemics in the field of marketing and researchers who are interested in conducting studies in the same field, it is hoped that this reseach can be the basis for further research. Based on the results of the study, of the 22 factors that influences student interest in entrepreneurship, it turns out that the most dominant are: The first factor consists of: being disciplined, high commitment, Creative Innovative, Leadership, Have a confident attitude, Productive character, Dare to take action, Reliable expertise, Have experience, Courage to face risks, and Independence. Second factor consists of: Being intersested in business opportunities and Foresight. The third factor consists of: Encouraging parent, Family support and Friends support. The fourth factor consists of: Support business partners, Friends support which is considered important and Cooperate with business partners. The fifth factor consists of: Realistic thinking and Perceived ease and careful planning.To enhance studenst’ interest in entrepreneurship, it is recommended to integrate entrepreneurship courses into the curriculum, organize structured entrepreneurship programs or workshops, provide training and mentoring bysuccesful business practitioners or alumni, foster collaboration with local business actors, develop softskills, organize extraculliculer activitities, offer financial support, establish business endeavors. Parent support and motivate their children to become entrepreneurs, because parents have a very strong rule in forming entrepreneurial interests.